Impact of potassium chloride on saltiness, bitterness, and other sensory characteristics in model soup systems - Hooge, Susan E. (Kansas State University, 2008)
The challenge with reduced sodium foods is finding a suitable sodium replacement that delivers a salty flavor without extraneous off flavors. Potassium chloride (KCl), a commonly used salt replacer, when used in conjunction with sodium chloride, can be perceived as salty; however to some people, KCl tastes bitter or metallic. The hypothesis for this research was the belief that a majority of people do not describe the flavors associated with KCl as bitter, metallic, or other possible negative terms. The objectives were 1) To determine the impact of KCl addition on the saltiness, bitterness, and other sensory characteristics in model soup systems using a trained descriptive analysis panel and 2) To determine what words are most frequently chosen by consumers to describe flavors associated with KCl. There were two studies conducted; 1) The first study examined the basic taste intensities in samples with varying levels (19%-41%) of total sodium ions and samples with a set total sodium ion level (19%) and varying levels of KCl (0%-0.75%) in model soup systems in order to understand the potential interaction of KCl on the perceived saltiness of NaCl. The degree to which KCl can be used in reducing total sodium ion levels without adversely affecting the basic taste sensory properties was also examined. Panelists evaluated the samples using the Sensory Spectrum® method. Salt, sour, bitter, umami, and metallic attributes were rated for chicken broth. Salt, sweet, sour, and bitter attributes were rated for tomato soup. 2) The second study examined the consumer language used to describe the flavors associated with KCl when used in a reduced sodium model soup system. Focus group participants generated the initial list of flavor descriptors for high (0.75%) KCl levels in chicken broth. A larger consumer study was conducted with subjects pre-screened for sensitivity to KCl Consumers were given reduced sodium chicken broth or tomato soup without KCl and another sample with 0.45% KCl, labelled Flavor A. Subjects then chose all of the descriptors from a pre-selected list that describe Flavor A, the flavors associated with KCl. Comparisons in language descriptor selection were made among ethnic groups (African American, Hispanic, Caucasian, and Asian), gender, and age groups. As an example, among ethnic groups, for chicken broth, Hispanics chose the salty descriptor less frequently than the other ethnic groups, whereas Asians chose the salty descriptor more frequently than the other ethnic groups. The trained descriptive analysis panel did not find an increase in bitterness perception as KCl levels increased. Consumers frequently selected characterizing flavor terms to describe flavors associated with KCl and rarely selected bitterness, metallic or other potentially negative terms to describe KCl flavor. The significance of these findings is that there may be a higher potential for sodium reduction in the food industry using KCl as a sodium ion replacer.
Keywords: Potassium chloride sensitivity; Sodium reduction in soups; Consumer language; Descriptive analysis; Agriculture, Food Science and Technology (0359); Health Sciences, Nutrition (0570)